Scholarship and Education in Islamic Law and Economics: The Challenges of Comparative Law (Fiqh al-Muqāran) - Necmettin Kızılkaya (Türkiye İslam İktisadı Dergisi)
The method, which is commonly acknowledged in Islamic studies and education of Islamic sciences, is to examine knowledge through inter-madhhab approach. This approach traces its origins to the mid-19th century and became widespread in the 20th century. A critique of this method, which is almost undisputed today, needs to be done and what it has gained or lost should be examined. The disciplines, which have successfully guided the culture of Islamic civilization in a wide range of areas from law to politics, from economics to literature, and from art to philosophy, cannot provide solutions to the problems of humanity today, a fact that should be addressed. This consequence leads us to the question of how the education of Islamic law is practiced, or how knowledge of Islamic law is produced. So, my point of departure will be this question. Since Islamic economics is also taught or practiced through Islamic law, I will use it as my sample. I will deal with the current situation, and then I focus on the question of what happened in the 20th century that led Muslim scholars to adopt a new method to study and teach Islamic sciences and economics. In doing so, I will question whether there has been such an approach in past centuries, and I will examine whether this new method has been successful or not. Finally, I will focus on an alternative method.